Characterization of the bioaccumulation and toxicity of copper pyrithione, an antifouling compound, on juveniles of rainbow trout - Bourdon, Charlotte; Cachot, Jérôme; Gonzalez, Patrice; Couture, Patrice (Peer Community Journal)

(untitled)
Since the global ban on tributyltin in antifouling paints in 2008 by the International Maritime Organization, new products have been developed and brought to the market. Among them, copper pyrithione (CuPT) is used, but its mechanisms of toxicity remain little known. This project aimed to identify and measure the impacts of aqueous exposure to CuPT, an organic compound, and compare it to ionic Cu2+ added in the form of its inorganic salt CuSO4, in equivalent Cu2+ molar concentrations, on rainbow trout (Oncorhynchus mykiss) juveniles under controlled laboratory conditions. A 24-hour acute exposure was performed with nominal concentrations of 50 and 100 µg/L Cu from either CuSO4 or CuPT (labelled CuSO4_50, CuSO4_100, CuPT_50 and CuPT_100, respectively). The CuPT_100 condition induced 85 % mortality in 15 hours and the CuPT_50 condition induced 5 % mortality in the same period. A chronic exposure was then performed with nominal concentrations of 1 and 10 µg/L Cu from CuPT and 10 µg/L Cu2+ from CuSO4 (labelled CuSO4_1, CuSO4_10, CuPT_1 and CuPT_10, respectively). Measured aqueous concentrations of Cu2+ were slightly higher than nominal concentrations for the lower concentrations, but lower for the CuPT_10 condition. The 8- and 16-day toxicokinetics showed a greater accumulation of copper in the gills of fish exposed to CuPT compared to fish exposed to Cu2+ from CuSO4. The CuPT_10 condition induced 35 and 38 % mortality after 8 and 16 days of exposure, while no mortality was observed in the CuSO4_10 condition. The growth of juveniles was not impacted during the 16 days of exposure for any condition. The activity of antioxidant enzymes (CAT, SOD, GPx) did not respond to exposure to either contaminant. The expression of genes involved in the antioxidant response (sod1, sod2, gpx), detoxification (cyp1a, mt1x, mt2x), Cu transport (ctr1, ctr2, slc11a2), energy metabolism (AcoAc, cox, 12S) and cell cycle regulation (bax) strongly decreased at Day 8 in the gills and at Day 16 in the liver of CuPT-exposed fish in comparison to controls at the same time point. This study clearly showed that the toxicity of Cu in the form of CuPT was much higher than that of ionic Cu from CuSO4and provides new information on the compound that will be useful to develop regulations concerning its use and release in the aquatic environment.